The "Akopian" vault performed by elite male gymnasts: Which biomechanical variables are related to a judge's score? - Farana, R.; Uchytil, J.; Zahradnik, D.; Jandacka, D. (Acta Gymnica, 2015)
Background: A vaulting performance takes a short time and it is influenced by and affects the quantity of mechanical variables. The significant relationships between the vaulting score and specific aspects of the gymnast's vault should conduct coaches to monitor these variables as a part of training or routine testing.